Prison religion: faith-based reform and the constitution - Sullivan, Winnifred Fallers (Princeton University Press, 2009)
More than the citizens of most countries, Americans are either religious or in jail--or both. But what does it mean when imprisonment and evangelization actually go hand in hand, or at least appear to? What do "faith-based" prison programs mean for the constitutional separation of church and state, particularly when prisoners who participate get special privileges? In Prison Religion, law and religion scholar Winnifred Fallers Sullivan takes up these and other important questions through a close examination of a recent trial challenging the constitutionality of a faith-based residential rehabilitation program in an Iowa state prison, a trial in which she served as an expert witness for the prisoner-plaintiffs